Urinary Elimination of Coproporphyrins Is Dependent on ABCC2 Polymorphisms and Represents a Potential Biomarker of MRP2 Activity in Humans. (17th April 2011) - Benz-de Bretagne, Isabelle; Respaud, Renaud; Vourc'h, Patrick; Halimi, Jean-Michel; Caille, Agnès; Hulot, Jean-Sébastien; Andres, Christian R.; Le Guellec, Chantal
Abstract : MRP2 encoded by ABCC2 gene is involved in the secretion of numerous drugs and endogenous substrates. Patients with Dubin-Johnson syndrome due to mutation in ABCC2 gene have elevated urinary coproporphyrin ratio (UCP I/(I + III)). Here we investigated whether this ratio could serve as a biomarker of MRP2 function. Phenotype-genotype relationships were studied in 74 healthy subjects by measuring individual UCP I/(I + III) ratio obtained on 24-hour urine and by analyzing five common SNPs in ABCC2 gene. The UCP I/(I + III) ratio varied from 14.7% to 46.0% in our population. Subjects with 3972TT genotype had a higher ratio (P = .04 ) than those carrying the C allele. This higher UCP I/(I + III) ratio was correlated with a higher level of isomer I excretion. This study provides a proof of concept that UCP I/(I + III) ratio can be used as a biomarker of MRP2 function in clinical studies as it provides quantitative information about the in vivo activity of MRP2 in a given patient.